Metabolic Food Waste and Ecological Impact of Obesity in FAO World's Region - Toti, Elisabetta; Di Mattia, Carla; Serafini, Mauro (Frontiers in Nutrition, 2019)
Obesity represents a titanic cost for the world's health systems but also a substantial ecological cost to the environment. High energy foods have been shown to be the major contributor to Greenhouse Gas (GHG) emissions, challenging the diet-environment-health triangle. The waste of resources and the unnecessary ecological cost due to an excessive consumption of foods leading to obesity have been ignored so far. Metabolic Food Waste [MFW(kg of food)] corresponds to the amount of food leading to Excess Body Fat (EBF) and its impact on the environment, expressed as carbon [MFW(kgCO2eq)], water [MFW(×10 L)] and land footprint [MFW(×10 m2)]. We aim to estimate the MFW(kg of food) in the seven FAO regions, Europe (EU), North America and Oceania (NAO), Latin America (LA), Sub-Saharan Africa (SSA), Industrialized Asia (IA), North Africa, West and Central Asia (NAWCA) and South and Southeast Asia (SSEA), and evaluate its impact on ecological footprints. The overall impact of MFW(tons of food) in the world corresponds to 140.7 million tons associated to overweight and obesity. Between the different regions, EU is responsible of the greatest amount of MFW(tons of food) volume (39.2 million tons), followed by NAO (32.5 million tons). In terms of ecological impact, EU and NAO displayed the highest values for all three MFW footprints, about 14 times more than SSA. We provide evidence of the enormous amount of food lost through obesity and its ecological impact. Reducing metabolic food waste associated with obesity will contribute in reducing the ecological impact of unbalanced dietary patterns through an improvement of human health.